Metal Complexes of π-Expanded Ligands (4): Synthesis and Characterizations of Copper(II) Complexes with a Schiff Base Ligand Derived from Pyrene - Luong, Xuan Dien (H. : ĐHQGHN, 2020)
An innovative π-expanded ligand derived from salicylaldimine ligand representing pyrene ring as a substitute for benzene ring was synthesized in 5 steps from commercially available pyrene. This unique bidentate ligand (1) was coordinated to Cu(II) metal centre for affording complex 2, which was characterized by IR, elemental, X-ray diffraction analyses, and magnetic susceptibility. Its coordination geometry is a trans-square plane with an obvious stair-step structure which is formed by two pyrene moieties and the coordination plane (CuN2O2). In addition, the dihedral angle between the coordination plane and the pyrene ring is 34.9o and the plane of seven carbon atoms of the long alkyl chains were arranged nearly parallel to the pyrene rings. The electronic properties of this novel complex 2 were examined via cyclic voltammetry and absorption spectroscopy to show the narrower HOMO-LUMO gap than those of the complex 4. Moreover, the particular behavior of both complexes 2 and 4 was investigated through DFT studies.